Integration of Website, RSS Feed, and Digital Signage to Support Public Information Relay Between Villages in Nusalaut District - Salamoni, Thenny; Suatkab, Syukri Gazali; Tupalessy, Johanis; Ismail Pellu, Deny (International Journal of Science, Technology & Management, 2026)
The rapid development of information technology has significantly influenced how information is distributed and accessed by communities. However, many rural areas still rely on conventional information media such as bulletin boards and printed announcements, which are inefficient and difficult to update. This research aims to design and implement an integrated public information system using websites, RSS feeds, and digital signage in Nusalaut District, Central Maluku Regency, Indonesia. The study uses a Research and Development (R&D) approach consisting of requirement analysis, system design, implementation, and system testing. The developed system integrates multiple village websites with RSS feed technology and cloud-based digital signage using Raspberry Pi as the media player. The results show that three digital signage units were successfully implemented in Nusalaut District Office, Ameth Village, and Nalahia Village. In addition, seven village websites and one district portal website were developed to support information distribution. The integration of RSS feed technology allows real-time relay of information from the district portal to digital signage and village websites. The proposed system improves the efficiency, accessibility, and timeliness of public information dissemination in rural areas.